Polyphasic characterization of a novel hot-spring cyanobacterium Thermocoleostomius sinensis gen et sp. nov. and genomic insights into its carbon concentration mechanism - Jiang, Ying; Tang, Jie; Liu, Xiangjian; Daroch, Maurycy (Frontiers in Microbiology, 2023)
Thermophilic cyanobacteria play a crucial role as primary producers in hot spring ecosystems, yet their microbiological, taxonomic, and ecological characteristics are not extensively studied. This study aimed to characterize a novel strain of thermophilic cyanobacteria, PKUAC-SCTA174 (A174), using a combination of traditional polyphasic methods and modern genomic-based approaches. The study included 16S rRNA-based phylogeny, ITS secondary structure prediction, morphological and habitat analyses, as well as high-quality genome sequencing with corresponding phylogenomic analyses. The results of the 16S rRNA, 16S-23S ITS secondary structure, morphology, and habitat analyses supported the classification of the strain as a member of a novel genus within the family Oculatellaceae, closely related to Albertania and Trichotorquatus. Genomic analysis revealed the presence of a sophisticated carbon-concentrating mechanism (CCM) in the strain, involving two CO2 uptake systems NDH-I3, and NDH-I4, three types of bicarbonate transporters (BCT1, bicA, sbtA,) and two distinct putative carboxysomal carbonic anhydrases (ccaA1 and ccaA2). The expression of CCM genes was investigated with a CO2 shift experiment, indicating varying transcript abundance among different carbon uptake systems. Based on the comprehensive characterization, the strain was delineated as Thermocoleostomius sinensis, based on the botanical code. The study of the complete genome of strain A174 contributes valuable insights into the genetic characteristics of the genus Thermocoleostomius and related organisms and provides a systematic understanding of thermophilic cyanobacteria. The findings presented here offer valuable data that can be utilized for future research in taxogenomics, ecogenomics, and geogenomics.